Penerapan Algoritma AES dan DSA Menggunakan Hybrid Cryptosystem untuk Keamanan Data - Suci Ramadani; Diana Diana; Siti Sauda (JURIKOM (Jurnal Riset Komputer), 2020)
Exchange of documents based on a computer such as exchanges of messages via email on the internet has been done as a commercial transaction. Although it looks practice but there are also so many negative impacts that occur. This is the message sent can be opened by anyone who has access to enter the email. So that it can lead irresponsible people to steal information of documents. To ensure the documents sent are authentic until the intended part, one way that can be done is to use cryptography. In this study applying cryptography of AES and DSA algorithms. AES algorithm is a symmetry key that is using the same key to process of encryption and decryption while DSA algorithm is an asymmetric key which is the process of encryption using a private key and using public key for decryption. Then use a hybrid algorithm to combine AES and DSA algorithm. The results of this study is an application of encryption and decryption with a success rate of 86% for file encryption and 83% for decryption. File size after encrypted has increased by 32% and return to its original size after decrypted